1998
DOI: 10.1111/j.1398-9995.1998.tb03904.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms, bronchial responsiveness, and cellular characteristics of induced sputum in elite swimmers

Abstract: To investigate respiratory symptoms, increased bronchial responsiveness, and signs of airway inflammation in elite swimmers, we examined 29 swimmers from the Finnish national team and 19 healthy control subjects (nonasthmatic, symptom‐free). They answered a questionnaire and were interviewed for respiratory symptoms. Lung volumes were measured and bronchial responsiveness assessed by a histamine challenge test. Induced sputum samples were also collected. Fourteen (48%) of the swimmers and three (16%) of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
156
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(171 citation statements)
references
References 29 publications
13
156
0
2
Order By: Relevance
“…In another study, total asthma (current asthma, physician-diagnosed asthma or BHR) was found in 23% of the athletes compared with 4% of the controls, current asthma in 14% compared with 2% among controls and positive skin prick test (SPT) in 48% of the athletes compared with 36% among controls (28). High prevalence of BHR (48%) to histamine was also found among swimmers (29). Maiolo et al (30) reported the prevalence of asthma in 15% and atopy in 18% of 1060 Italian competing summer athletes.…”
Section: Asthma and Bhr Among Athletesmentioning
confidence: 91%
See 1 more Smart Citation
“…In another study, total asthma (current asthma, physician-diagnosed asthma or BHR) was found in 23% of the athletes compared with 4% of the controls, current asthma in 14% compared with 2% among controls and positive skin prick test (SPT) in 48% of the athletes compared with 36% among controls (28). High prevalence of BHR (48%) to histamine was also found among swimmers (29). Maiolo et al (30) reported the prevalence of asthma in 15% and atopy in 18% of 1060 Italian competing summer athletes.…”
Section: Asthma and Bhr Among Athletesmentioning
confidence: 91%
“…In young competitive skiers as compared with healthy somewhat older medical students, not particularly physically active, the skiers had lymphoid aggregates in their bronchi and signs of bronchial remodelling (tenascin) as demonstrated by bronchial biopsies in addition to increased responsiveness to cold air (5,64). A mixed type of eosinophilic and neutrophilic inflammation was found in elite swimmers (29,65), ice-hockey players (66) and cross-country skiers (64,67,68). Swimmers with exercise-induced bronchial symptoms had significantly higher sputum eosinophil counts than symptom-free swimmers (29).…”
Section: Effects Of Heavy Exercisementioning
confidence: 99%
“…Studies in athletes are in line with this observation. Helenius et al have reported increased levels of eosinophils and neutrophils, as well as increased concentrations of sputum eosinophil peroxidase and human neutrophil lipocalin in induced sputum from swimmers [13]; Sue-Chu et al reported lymphoid aggregates in endobronchial biopsies from skiers [14], suggesting increased airways inflammation due to training as well as a wearand-tear effect caused by increased ventilation during endurance training [15].…”
mentioning
confidence: 99%
“…Other environmental triggers include chlorine in swimming pools [13,14] chemicals from resurfacing ice hockey rinks [15], and in urban areas from automobile exhaust [16]. EIB may be underestimated as athletes have been shown to be poor perceivers of bronchospasm [17,18] and lack awareness of symptoms [19,20].…”
Section: Epidemiologymentioning
confidence: 99%